Management of refractory bleeding post-cardiopulmonary bypass in an acute heparin-induced thrombocytopenia type II renal failure patient who underwent urgent cardiac surgery with bivalirudin (Angiox®) anticoagulation. (April 2018) - Hassen, Kimberly; Maccaroni, Maria R.; Sabry, Haytham; Mukherjee, Smitangshu; Serumadar, Shankari; Birdi, Inderpaul
Acute heparin-induced thrombocytopenia (HIT) patients present a myriad of anticoagulation management challenges, in clinical settings where unfractionated heparin (UFH) is the traditional drug of choice. UFH use in cardiac surgery is a known entity that has been subject to rigorous research. Research has, thus, led to its unparalleled use and the development of well-established protocols for cardiac surgery. In comparison to UFH, bivalirudin use for acute HIT patients requiring urgent cardiac surgery with cardiopulmonary bypass (CPB) is still in its infancy. We describe the tailored post-CPB management of refractory bleeding in a 65-year-old infective endocarditis, acute HIT patient with renal failure who underwent urgent aortic valve replacement and mitral valve repair with bivalirudin anticoagulation. A management approach that entailed a combination of continuous venovenous haemofiltration (CVVH), 4-Factor prothrombin complex concentrate (PCC) (Beriplex), recombinant factor VIIa (rFactor VIIa) and desmopressin (DDAVP) were consecutively used post-operatively in theatre. Based on this case study experience, two modifications to institutional protocols are recommended. The first is the use of CVVH in theatre to eliminate bivalirudin in renal failure patients or in patients where bivalirudin elimination is prolonged. Secondly, a 'rescue therapy/intervention' algorithm for the swift identification of refractory bleeding post-CPB is also recommended. Rescue therapy agents, such as a 4-Factor PCCs and rFactor VIIa, should be incorporated into the protocol after a robust evidence-based search and agreement with the haematologist. The aim of these recommendations is to reduce the risk of bleeding associated with bivalirudin use for inexperienced institutions and experienced institutions alike, until larger randomized, controlled studies provide more in-depth knowledge to expand our clinical practice.